Undergraduate medical curriculum ofUniversiti Sains Malaysia in terms of Harden's ten questions of cuniculum development - Hafiza, Arzuman (Pusat Pengajian Sains Perubatan, 2010)
The curriculum of School of Medical Sciences (SMS), Universiti Sains Malaysia (USM) has been developed to produce community oriented doctors who are competent to manage a patient holistically. The block based spiral curriculum with three Phases makes it distinctive from other medical programme of the country for its unique features .. Purpose: To explore the extensibility of the curriculum in response to Harden's 10 questions of curriculum development Method: This article analysed the USM medical curriculum in terms of Harden's 10 questions of curriculum development. The 10 questions is a comprehensive guide for curriculum development and a well developed curriculum must address all the questions. Discussion: The critical analysis showed the USM medical curriculum successfully addressed Harden's all 10 questions. The undergraduate medical curriculum is characterized by the features of SPICES and stands on the uniqueness of integration, problem based and spiral approach. The spiral concept enables the school to implement the horizontal and vertical integration of the different disciplines/subjects within the three Phases. The Community and Family Case Study (CFCS) programme is providing community oriented training, another unique aspect of the curriculum. It also enables with an encouraging educational environment which is favourable for its operation and profoundly influencing the outcome of the programme Conclusion: Established in 1979, the SMS currently has more than 1,000 undergraduate students with nearly 300 full time academic staff. This SMS is committed to enhance the competitive nature of the students by promoting their intellectual and educational quests, providing confidence for continuing study and a sense of social accountability.